2011
DOI: 10.1093/carcin/bgr210
|View full text |Cite
|
Sign up to set email alerts
|

Colon tumour cells increase PGE2 by regulating COX-2 and 15-PGDH to promote survival during the microenvironmental stress of glucose deprivation

Abstract: Due to poor tumour-associated vasculature, tumour cells are subjected to a fluctuating microenvironment with periods of limited oxygen and glucose availability. Adaptive mechanisms to adverse microenvironments are important for tumour cell survival. The cyclooxygenase (COX)-2/prostaglandin E(2) (PGE(2)) pathway has key roles in colorectal tumorigenesis. Although glucose is important as an energy source and in maintaining endoplasmic reticulum homeostasis, relatively little is known regarding how tumour cells a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
52
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 39 publications
1
52
0
Order By: Relevance
“…The loss of 15-PGDH expression may also result from impaired TGF-Ī² signaling, a common event in colon and gastric cancers (42)(43)(44). While published data support the concept that 15-PGDH plays a direct role in controlling epithelial cell proliferation and colony-forming capacity, it has also been suggested that disruption of 15-PGDH expression may be a required or important step for cancer cell adaptation to the hypoxic tumor microenvironment and may promote survival under the microenvironmental stress of glucose deprivation (11,15). Furthermore, there is also a link between tumor-induced immunosuppression and a deficiency of 15-PGDH expression, with loss of 15-PGDH in tumor-infiltrating myeloid cells leading to immune evasion (45).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The loss of 15-PGDH expression may also result from impaired TGF-Ī² signaling, a common event in colon and gastric cancers (42)(43)(44). While published data support the concept that 15-PGDH plays a direct role in controlling epithelial cell proliferation and colony-forming capacity, it has also been suggested that disruption of 15-PGDH expression may be a required or important step for cancer cell adaptation to the hypoxic tumor microenvironment and may promote survival under the microenvironmental stress of glucose deprivation (11,15). Furthermore, there is also a link between tumor-induced immunosuppression and a deficiency of 15-PGDH expression, with loss of 15-PGDH in tumor-infiltrating myeloid cells leading to immune evasion (45).…”
Section: Methodsmentioning
confidence: 99%
“…The human PGDH gene is located on chromosome 4 and encodes a 29-kDa protein. 15-PGDH is highly expressed in normal colon epithelia but the expression is decreased in colon cancers (12)(13)(14)(15). 15-PGDH has a demonstrated tumor suppressor activity in lung cancer and breast cancer (16,17), and overexpression of 15-PGDH inhibits growth of colon tumor xenografts in immune-deficient mice (13).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stress also activates the unfolded protein response system that ultimately activates survival proteins such as the heat shock protein Hsp90 (Saito et al, 2009). Additionally, prolonged hypoglycaemic stress has been known to contribute to oncogenic mutation (Yun et al, 2009) and activate survival pathways, including the PI3K/AKT pathway (Roberts et al, 2011). Given these survival phenotypes, it is reasonable to hypothesize that low extracellular glucose levels could increase drug resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Mutation of PGDH was associated with high level of prostaglandin E2 and congenital osteoarthricular hypertrophy (cite) (Thill et al, 2010;Young et al, 2013). Furthermore, high physiological level of PGDH was found in various normal human epithelial tissue, including lung (Ding et al, 2005;Tai et al, 2007;Li et al, 2014), colon (Chi et al, 2009;Roberts et al, 2011), stomach and breast (Brocklehurst et al, 1986). The expression of PGDH in normal human tissue helps control of the level of prostaglandins, which are produced by protumorigenic enzymes including cyclooxygenase-2.…”
Section: Introductionmentioning
confidence: 99%